(untitled) (Indian Journal of Child Health, 2021)
Background: Paucity of data on adolescent polycystic ovary syndrome (PCOS) from South India. Objective: The objective of the study was to describe the clinical and biochemical profile of PCOS and its relationship to cardiometabolic risk in obese adolescent girls. Materials and Methods: A prospective observational study was conducted on adolescent girls attending obesity clinic over a 3-year period. Overweight and obese adolescent girls diagnosed as PCOS (based on Rotterdam criteria) were considered as Group I and without PCOS considered as Group II. A detailed history, physical examination, markers of hyperandrogenism, and metabolic profile were assessed and compared in two groups. Prevalence of metabolic syndrome and individual cardiometabolic risk factors was ascertained. All subjects were initiated on lifestyle measures and medications as clinically indicated. Results: Thirty-three girls with PCOS (Group I) and 33 without PCOS (Group II) were recruited. About 72.7% of subjects showing oligo or anovulatory cycles, 51.5% showed biochemical hyperandrogenism (mean testosterone level 36.76 ± 9.86 ng/dL), 69.7% showed clinical hyperandrogenism, and 84.5% showed radiological evidence of PCOS. The percentages of subjects fulfilling two and all three criteria of Rotterdam criteria for PCOS were 75.75% and 24.24%, respectively. Total 36% of the subjects had positive family history. Hirsutism was present in 54.54% (mean Ferriman-Gallwey score 8.6 ± 2.17). Percentage of subjects with individual metabolic abnormalities increased across the tertiles of BMI irrespective of the presence of PCOS. Conclusion: The profile of PCOS in obese South Indian adolescent girls is described. All overweight and obese adolescent girls should be screened for metabolic abnormalities, irrespective of the presence of PCOS.